A new approach to improving the accuracy of elemental analysis in laser mass spectrometry. Issue 4 (August 2017) - Milyaeva, Violetta V; Sil'nikov, EE; Mikhailov, AM; Sysoev, Alexander A
It is shown that the main reason affecting the accuracy and reproducibility of the elemental analysis of solids with a laser source of ions is the difference in the ionization cross sections of different elements in the generation of laser plasma. Computer modeling was carried out for the evaporation of the sample and generation of laser plasma at different values of laser power density. The aim of modelling was to determine the cause of the low accuracy of analysis by direct selection of ions from the plasma. The researches have shown that we cannot get satisfactory accuracy of analysis using analytical signal formed only on the base of single-charged ions. At the same time, in the formation of an analytical signal, as a sum of the intensities of the mass peaks of all charges of each element, the accuracy of the analysis does not depend either on the ionization cross section or on the nonreproducibility of the laser radiation power. It is shown that this approach completely eliminates the "matrix effect."